Temperatures effects on cascaded Mach-Zehnder interferometer structures - Ary Syahriar; Rahmat Alamtaha; Zulkifli Alamtaha; Putri Wulandari (Institute of Advanced Engineering and Science, 2020)
To increase bandwidth and number of channels per fiber for more than one wavelength in the same fiber the dense wavelength division multiplexing (DWDM) technology has been utilized. One of the devices that are important in DWDM is an optical interleaver. This paper discussed the effects of temperatures in the DWDM interleaver by using the Mach-Zehnder interferometer (MZI) structures which is arranged in two-stage cascaded MZI and the three-stage cascaded MZI geometries. The main consequences of increase temperature inside the fiber optics are the change of effective refractive index in the material of silica fiber due to the thermo-optics effects. In our analysis we have used the transfer matrix method to investigate the wavelength dependence of output power to the temperatures changes that varies from 30oC to 430ºC. In the calculation we have used the C-Band range wavelength which is around 1530 to 1565 nm. It has been shown that the change of temperatures may shift the wavelength inside the MZI output power in linear manners. These effects may be used to tune wavelength transmission inside the MZI structures to suit the ITU-T defined grid.